Expect the unexpected : risk measurement and management in commercial real estate - Furfine, Craig (London : Kellogg School of Management, 2017)
In early December 2013, Roxann Biller, Associate at the Chicago-based private equity firm Delta Quantitative Real Estate Capital, was asked to assess the risk associated with the firm's first potential overseas investment. Haifu Senta? Gendaino (HSG) was a large multi-tenant logistics property located in the Gaikando area of Tokyo. High-quality tenants currently occupied the property, so at first glance the risks of investing in the property seemed minimal. However,Biller knew that she had to consider the potential drawbacks. This would mean gaining a better understanding of each tenant, trying to forecast the future condition of the Tokyo logistics market, and considering what new risks her firm would face because the property's cash flows were in a foreign currency.
Originally Published InFurfine, C. (2017). Expect the unexpected: Risk measurement and management in commercial real estate. 5-315-310. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Biller, Roxann; Delta Quantitative Real Estate Capital; Commercial real estate; Real estate investment; Investments, Foreign; Risk